Mammary echography in ewes as a tool to evaluate udder abnormalities and its relationship with performance of their progeny - Castillo-Hernández, Gabriela (2022)
The ultrasound structure of the udder in sheep was evaluated as a tool for monitoring mammary health and its relationship with the productive performance of the progeny. Twenty-two females and their respective offspring were randomly selected. An ultrasound evaluation and the Image J® 1480 program were performed for image analysis. In the udders, the type of tissue, consistency and presence of abscesses were measured. Body condition score, age and breed type were recorded in the dams, and birth weight, weaning weight and daily weight gain were recorded in lambs. The information was evaluated through analysis of variance, correlation analysis and multiple regression. A significative effect was found in the number of pixels per ultrasound slice (p<0.05), with the highest number of pixels in parenchyma and soft tissue. Effect of age and breed type on the number of pixels was observed. The lowest number of pixels was observed in abscesses and cistern tissue compared to parenchyma (p<0.05). A significative effect of body condition was found when udder consistency, age and breed type was considered (p<0.05). All study variables were significant in the regression model (p<0.05), where the variables that explain the greatest variability are type of tissue and body weight gain. The number of pixels tends to increase in healthy udders. It is concluded that ultrasound in sheep can be used as an indicator of mammary health with a strong relationship with daily weight gain of the lambs.